Tourism experiences of persons with disabilities in Malaysia – voices of mobility-impaired people - Saad, Mazni; Muhammad Goh Kee Leok, Ameen Noor Aqilah (Infrastructure University, 2024)
Tourism is a universal right for everyone, including Persons with Disabilities (PwDs). However, tourism experiences of PwDs, especially individuals who have mobility impairments, are often hindered by barriers and obstacles in their paths. A huge part of the tourism destinations still has not been accessible for mobility impaired people to explore and experience nature and culture. This study brings up the topic of the tourism experiences of the mobility impaired people in Malaysia. Deploying qualitative methods of research, phenomenological approach is applied through four semi-structured online interviews with mobility impaired PwDs informants through purposive snowball sampling. This study is deployed to record the tourism experiences of PwDs and to investigate the challenges faced by PwDs in terms of facilities, services and support when taking part in tourism activities, additionally to identify the expectations of PwDs for their future participation in tourism activities. This study spotlights the participation experiences of mobility impaired individuals in events in Malaysia and, as a practical implication, this study recommends a future direction of accessibility guidelines for event organizers in Malaysia to implement accessibility in their events. The results of this study reflect the challenges of PwDs are mostly the concerns of inability to travel alone and lack of support from event organizers or hosts during their participation.